Diplomacy in the context of the Russian invasion of Ukraine: Continuation of war by other means - Sabine Fischer (Stiftung Wissenschaft und Politik (SWP), 2023)
Direct negotiations on a ceasefire in Russia's war against Ukraine broke down within just a few months. Today, Moscow and Kyiv are pursuing diplomatic initiatives in order to shape the international context of the war in their favour. Russia's war diplomacy aims to weaken the "collective West" at the global level as part of its strategy to bring external support for Ukraine to a halt. Ukraine is seeking to isolate Russia internationally. Meanwhile, Russia's illegal war of aggression continues. If there is to be even a possibility of ceasefire negotiations in the future, Germany and its partners must carry on providing military support to Ukraine.
Keywords: 320; Russia; Ukraine; War on Ukraine; peace negotiations; ceasefire; diplomacy; Bakhmut; Black Sea Grain Initiative; BSGI; Grain from Ukraine; collective West; anti-colonialism; BRICS; peace formula; Kyiv Security Compact; security commitments; security guarantees